A SmartPLS4-based CB-SEM confirmatory factor analysis: A case of speaking needs for Chinese business English undergraduates - Ke Hu; Asmaa AlSaqqaf (Castledown Group Pty Ltd, 2025)
Over the past decade, there has been an increasing emphasis on English for Specific Purposes (ESP) within China’s higher education language programs. However, the shift towards ESP presents a multifaceted challenge, particularly for business English teaching at higher education, where speaking proficiency is crucial yet often falls below expectations. Considering these issues, the authors of this study developed a scale based on relevant literature to pinpoint students' needs for Oral Business English (OBE) instruction, and to explore the interplay among constructs within the scale that define these needs. This quantitative study employed a two-phase approach, utilizing separate datasets and different sample sizes of Chinese business English undergraduates selected through simple random sampling. Phase one (N = 52) leveraged SPSS 29 for exploratory factor analysis (EFA), while phase two (N = 396) utilized SmartPLS4 for covariance-based structural equation modeling (CB-SEM) in confirmatory factor analysis (CFA). The findings reveal that the undergraduate respondents grapple with a total of five distinct needs related to OBE instruction. These include three target needs: difficulties in oral communication, oral challenges in collaborative engagement, and required speaking activities. Additionally, there are two learning needs: perceived learning styles and perceived course satisfaction. Significantly, as perceived by these undergraduate respondents, each of these needs was found to have a substantial impact on the effectiveness of OBE instruction in China.